The Influence of Animation Programmes on Tourists' Satisfaction: The Role of Animators - Sanja Pekovic; Aleksandra Djekic; Vasilije Markovic; Milica Bojbasa; Djurdjica Perovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Animation programmes represent a specific range of services and facilities that complement and improve the overall range of tourism service. Animation activities provide a wide range of services that are intended to provide more than expected for tourists. Therefore, to respond to tourists' various requests and needs, the role of animators in animation programmes is essential. In other words, tourists' satisfaction could be achieved via the tourist animators' competences, since they are intended to make the stay at the tourist destinations as pleasant as possible. However, it is necessary to note that there is a large gap in the literature concerning the importance of animation programmes and animators for tourism services. To overcome this deficit in the literature, this paper analyses the influence of different animator competences on the tourists' satisfaction to determine their importance for the tourist services. Using the Tobit model on a sample of 30 tourists, the results show that the relation between tourists' satisfaction and animator competences associated with patience, qualification, and organization, is positive and statistically significant. Based on the obtained results, we have suggested mechanisms for further development in this field, focusing on the constant improvement of the animator competences and animation programmes.